The association of migration experiences on the self-rated health status among adult humanitarian refugees to Australia: an analysis of a longitudinal cohort study - Alison Dowling; Joanne Enticott; Marina Kunin; Grant Russell (BMC, 2019)
Abstract Background Refugees are potentially at an increased risk for health problems due to their past and current migration experiences. How migration factors shape refugee health is not well understood. We examined the association between migration factors and the self-rated general health of adult humanitarian refugees living in Australia. Methods We analyzed the first three waves of data from the 'Building A New Life In Australia' longitudinal survey of 2399 humanitarian refugees resettled in Australia. The study outcome was self-rated health measured by the 36-Item Short Form Health Survey. Predictors were migration process and resettlement factors. We used generalized linear mixed models to investigate the relationship between predictor and outcome variables. Results Poor general health persisted among this refugee population at high levels throughout the three-year follow-up. At baseline, 35.7% (95% CI: 33.8-37.7%) of the study population reported poorer general health. Female gender, increasing age and post-migration financial stressors were positively associated with poorer general health. Having a university degree and absence of chronic health conditions were seemingly protective against declining general health (OR: 0.50; 95% CI: 0.65-1.81 and OR: 0.15, 95% CI: 0.09-1.04, respectively). Conclusion Our results show that there is persisting high prevalence of poorer general health among adult refugees across the initial years of resettlement in Australia. This finding suggests unmet health needs which may be compounded by the challenges of resettlement in a new society, highlighting the need for increased clinical awareness of this sustained health burden to help inform and prepare refugee health care and settlement service providers.